Innovative accounting teaching : an action research project - Smith, Wilhelmina (Welkom: Central University of Technology, Free State, 2002)
Accounting is a form of communication, or the language of economic activity which has its own vocabular y and terminology. Accounting is thus categorised as the mode of communicating f inancial information about business activities and can be termed ~the language of the business world'. Business activities present a continuous circular flow which has to be communicated by making use of words and numbers , through the principles and procedures of Accounting. Accounting, thus involves standard methods o f keeping records of all financial occurrences affecting a business concern. Modern societies expect of education to prepare young people for their envisioned roles and responsibilities in life. Unfortunately many parents realize that the vocational opportunities of their children are not guaranteed, even with matric certificates and they realize that the best alternative option would be to start a family bus iness. Commercial subjects were introduced into schools with the primary aim of I complementing vocational training and these subjects could be specifically useful t o those aspiring to run a business . Unfortunately, very few learners offer Accounting as a matric subject. The compl aint concerning the subject is that the content taught at school is too theoretical and far-removed from Accounting practice. Beginner teachers are also faced with a dilemma that they virtually have no experience of the practical implementation of Accounting. Present research is intended to be used by teachers in school context for Grade 8 to 10. The purpose of this research is to attempt to motivate more learners to take Accounting with the intention to teach this subject. Research methodology includes a thorough literature study in order to facilitate understanding of the research problem. This study focuses strongly on Action research as component of the qualitative method of research. Questionnaires were u tilized to ascertain what problems are experienced in the teaching of certain facets of Accounting. Interviews were also made use of to obtain information from key people. It is concl uded that teachers need assistance to teach Accounting. Innovative Accounting Teaching is designed to assist teachers with the implementation of the subject in a practical and easy-to-interpret way and could be used by student teachers, novice teachers as well as seasoned teachers .
Thesis
Keywords: Accounting